Simulating aerosol formation and effects in NOx absorption in oxy-fired boiler gas processing units using Aspen Plus - Schmidt, David Daniel (Kansas State University, 2013)
Oxy-fired boilers are receiving increasing focus as a potential response to reduced boiler emissions limits and greenhouse gas legislation. Among the challenges in cleaning boiler gas for sequestration is attaining the necessary purity of the CO[subscript]2. A key component in the oxy-fired cleaning path is high purity SO[subscript]x and NO[subscript]x removal, often through absorption using the lead-chamber or similar process. Aerosol formation has been found to be a source of product contamination in many flue gas absorption processes. A number of authors presented simulation methods to determine the formation of aerosols in gas absorption. But these methods are numerically challenging and not suitable for day-to-day analysis of live processes in the field. The goal of this study is to devise a simple and practical method to predict the potential for and effect of aerosol formation in gas absorption using information from Aspen Plus, a commonly used process simulation tool. The NO[subscript]x absorber in an oxy-fired boiler CO[subscript]2 purification system is used as a basis for this investigation. A comprehensive review of available data suitable for simulating NO[subscript]x absorption in an oxy-fired boiler slipstream is presented. Reaction rates for eight reactions in both liquid and vapor phases are covered. These are entered into an Aspen Plus simulation using a RadFrac block for both rate-based and equilibrium reactions. A detailed description of the simulation format is given. The resulting simulation was compared to a previously published simulation and process data with good agreement. An overall description of the aerosol formation mechanism is presented, along with an estimate of expected aerosol nuclei reaching the NO[subscript]x absorption process. A method to estimate aerosol quantities produced based on inlet gas nuclei concentration and available condensable water vapor is presented. To estimate aerosol composition and emissions, an exit gas slipstream is used to equilibrate with a pure water aerosol using an Aspen Plus Equilibrium Reactor block. Changing the composition of the initial aerosol feed liquid suggests that the location of aerosol formation may influence the final composition and emissions.
Keywords: Aerosol simulation absorber aspen; Chemical Engineering (0542)